Realistic deformation of 3D human blood vessels. (3rd May 2013) - Park, Jaesung; Shim, Minsub; Park, Seon‐Young; Kang, Yunku; Kim, Myung‐Soo
ABSTRACT: We present a real‐time algorithm for realistically deforming 3D human blood vessels, while automatically detecting and avoiding interference among a large number of blood vessels under deformation. Sweep surfaces are employed for this purpose. Using a dynamic bounding volume hierarchy, specially designed for sweep surfaces, we support collision detection and other related geometric computations in real time. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Using a dynamic bounding volume hierarchy for sweep surfaces, we present a real‐time algorithm for realistically deforming 3D human blood vessels, while automatically detecting and avoiding interference among a large number of blood vessels under deformation.